2021
DOI: 10.1371/journal.ppat.1010091
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian antiviral systems directed by small RNA

Abstract: There are strong incentives for human populations to develop antiviral systems. Similarly, genomes that encode antiviral systems have had strong selective advantages. Protein-guided immune systems, which have been well studied in mammals, are necessary for survival in our virus-laden environments. Small RNA–directed antiviral immune systems suppress invasion of cells by non-self genetic material via complementary base pairing with target sequences. These RNA silencing-dependent systems operate in diverse organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 135 publications
0
12
0
Order By: Relevance
“… 1 RNA silencing pathways have been identified as antiviral defense mechanisms in plants and insects, and possibly in mammalian cells. 2 To escape this antiviral defense, plant and insect viruses possess virus‐encoded suppressors of RNA interference, and this may extend to mammalian cells. 3 An interesting hypothesis to explain our findings is thus that SARS‐CoV‐2 targets cellular miRNA biogenesis.…”
Section: Figurementioning
confidence: 99%
“… 1 RNA silencing pathways have been identified as antiviral defense mechanisms in plants and insects, and possibly in mammalian cells. 2 To escape this antiviral defense, plant and insect viruses possess virus‐encoded suppressors of RNA interference, and this may extend to mammalian cells. 3 An interesting hypothesis to explain our findings is thus that SARS‐CoV‐2 targets cellular miRNA biogenesis.…”
Section: Figurementioning
confidence: 99%
“…Small RNAs (sRNAs) refer to a group of short (<200, and usually 18-30 nt in length) and non-coding RNA species. There are about seven families of sRNAs that mainly include microRNA (miRNA), small interfering RNA (siRNA), small nuclear RNA (SnRNA), small nucleolar RNA (snoRNA) and those derived from rRNA, tRNA, or fragments of transcribing genetic elements ( 14 , 15 ). Among them miRNAs and siRNA have been mainly studied for regulatory roles participating in various cellular processes, including RNA splicing, modification, degradation, and translational arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Among them miRNAs and siRNA have been mainly studied for regulatory roles participating in various cellular processes, including RNA splicing, modification, degradation, and translational arrest. Small RNAs, especially miRNA are known to modulate the cell response to virus infections ( 14 , 15 ). Studies have provided evidence that miRNAs are pivotal in modulating macrophage polarization, differentiation, cytokine production, and inflammatory regulation ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…YFV and other flavivirus capsid proteins have been reported to suppress the RNA interference pathway by binding to dsRNA [ 31 ]. While the role of RNA interference in combatting viral infection in mammals has been controversial, more recent data suggest that it may indeed be an effective arm of the innate immune response (reviewed in [ 53 ]). In another study, DEAD box helicase 3 X-linked (DDX3X) was identified as a DENV capsid-binding protein [ 32 ].…”
Section: Discussionmentioning
confidence: 99%